Ethnobotany study of potential and utilization of medicinal plants by local communities in Muara Enim Regency, South Sumatera - Yetty Hastiana; Novitasari Novitasari; Aseptianova Aseptianova; Sulton Nawawi (Mangifera Edu, 2023)
Ethnobotany of medicinal plants is a botanical science that studies using plants as drugs to treat a disease. This study aimed to determine the types of plants, processing methods, usage methods, and the use value (UV) of plants used as medicine by local people in Kayuara Sakti Village. The research method used is descriptive exploratory. The sampling technique used is purposive sampling. The research sample consisted of 49 people in Kayuara Sakti Village. They are collecting data using interviews, observation, and documentation. Data analysis in this study is qualitative and quantitative. The results of this study obtained the following data: (1) The types of medicinal plants used by local communities in Kayuara Sakti Village are 100 species belonging to 50 families. Diseases that are often treated are diseases that are commonly suffered by the community. (2) The method of processing medicinal plants is by boiling (44%), pounding/mashing (14), grated and squeezing (13%), brewing (7%), cooking and splitting (5%), without processing (4%), kneaded (3%), burned (2%), soaked, rolled, crushed, roasted and withered (1%). (3) The way to use medicinal plants is by drinking (57%), eating (16%), smearing (10%), dripping (3%), plugging and bathing (2%), and gargling, chewing, and rubbed (1%). (4) Use value (UV) medicinal plants used by the community are 0,02-0,81. The species with the highest value is turmeric (Curcuma domestica Val.).